Composite decolorizing agent for high-iron aluminosilicate glass and application method of composite decolorizing agent
By using composite decolorizer composed of CeO2, Co2O3 and Nd2O3 in high-aluminum cover glass, combined with low-cost SiO2 raw materials, the problem of high-aluminum cover glass is solved, and high light transmission is achieved Improvement of rate, whiteness and uniformity.
Patent Information
- Application Number
- CN202411670162.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
AI Technical Summary
The existing high-aluminum cover glass ensures high light transmittance and whiteness, while the production cost is high, and the uniformity and transparency of the glass are not ideal.
Using a composite decolorizer, including CeO2, Co2O3 and Nd2O3, high-iron aluminosilicate glass is prepared by adjusting the content of these oxides and combining low-cost SiO2 raw materials to achieve effective neutralization and transparency of the glass color. .
The light transmittance, whiteness and uniformity of the glass are improved, production costs are reduced, and stable control of the color of aluminosilicate glass is achieved under high-iron content.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass production, in particular to a composite decolorizing agent for high-iron aluminosilicate glass and an application method thereof. Background Art
[0002] At present, high-aluminum cover glass is the outermost protective glass used for smart touch phones, tablet computers, and smart touch terminal devices. It is required to have not only a high light transmittance T≥90%, but also a high "whiteness", that is, in the CIE1976 chromaticity coordinates L*a*b*, the a*b* value should be small, and the closer to 0 the better.
[0003] Iron content is the main factor affecting the color of glass, with Fe 2+ and Fe 3+ Existing in ionic form, Fe 2+ Can turn glass into blue-green, Fe 3+ Can turn glass into light yellow-green, Fe 2+ The coloring ability is about Fe 3+ The balance between them is directly affected by the furnace atmosphere and the redox index in the formula. Chemical decolorization is to eliminate the yellow color of glass contaminated by organic matter and to reduce the coloring ability of Fe 2+ Iron oxides are converted into Fe 3+ In order to use physical decolorization, usually by adding compounds such as selenium, Nd2O3, manganese, Co2O3, etc., they can produce purple or purple-red in the glass, which just complements Fe 3+ The yellow-green color further neutralizes the color, making it close to colorless and increasing the light transmittance of the glass.
[0004] The transmittance of ordinary glass is generally above 80%. For example, the transmittance of float white glass is generally 82-83%. The color cast is obvious, the relative values of colors in different areas on the glass vary greatly, the uniformity is low, and the transparency is not high and not clear enough. The transmittance of ultra-white glass can reach 91-93%. However, the lower the iron content in the glass raw materials, the higher its price. In order to ensure the whiteness and transmittance of high-aluminum glass, the iron content of its main component, silica sand, is usually selected from ultra-white sand with an iron content of less than 120ppm, which increases the production cost. At the same time, the reduction of iron oxide content in the glass will reduce the erosion of the kiln.
[0005] Therefore, it is necessary to provide a composite decolorizing agent for high-iron aluminosilicate glass and an application method thereof which can improve the transmittance and uniformity of glass, effectively remove the bad color of glass, and have low cost. Summary of the invention
[0006] The present invention provides a composite decolorizing agent for high-iron aluminosilicate glass and an application method thereof to solve the problems raised in the above background technology.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A composite decolorizer for high-iron aluminosilicate glass comprises a glass mixture of high-iron aluminosilicate glass and a composite decolorizer added to the glass mixture, wherein the composite decolorizer consists of CeO2, Co2O3 and Nd2O3, wherein the content of CeO2 is 0.05%-0.15% of the glass mixture, the content of Co2O3 is 1.5ppm-2.5ppm of the glass mixture, and the content of Nd2O3 is 0.01%-0.02% of the glass mixture.
[0009] Preferably, the glass mixture is composed of SiO2, Al2O3, Na2O, K2O, MgO, and ZrO2, wherein the content of SiO2 is 57%-64%, the content of Al2O3 is 13%-15%, the content of Na2O is 12%-14%, the content of K2O is 4%-6%, the content of MgO is 4%-7%, and the content of ZrO2 is 0%-1.5%. SiO2 is introduced from a high-iron raw material with low cost and high iron content, which is not limited here. According to the high-iron raw material with different iron content, the bad color in the produced glass can be neutralized by adjusting the proportion of each raw material of the composite decolorizer.
[0010] The SiO2 in the present invention is introduced by 800ppm of ordinary white sand, and the iron content of the prepared aluminosilicate glass is 590-660ppmm, showing a poor green color. By adding CeO2, Fe 2+ Fe 3+ The glass becomes lighter in color, and the blue-purple color produced by Co2O3 and Nd2O3 eliminates Fe 3+ The yellow-green color of the glass is improved, thereby improving the whiteness of the glass.
[0011] Preferably, a method for applying the composite decolorizing agent based on the high iron aluminosilicate glass as described above comprises the following steps:
[0012] 1) Weigh 1000g of glass mixture, and weigh the raw materials in the composite decolorizer in proportion to the weight of the glass mixture;
[0013] 2) placing the glass mixture and the raw materials of the composite decolorizing agent in a mixing device and mixing them for a certain period of time to form a glass and decolorizing agent mixture;
[0014] 3) placing the glass and decolorizing agent mixture into a crucible and heating it to a certain temperature for melting and processing, and after melting, lowering the temperature to a certain level for clarification and homogenization to form glass liquid;
[0015] 4) The clarified and homogenized glass liquid is poured into a mold to form a preliminarily formed glass, and the preliminarily formed glass is placed in a heating device to gradually anneal and cool to room temperature at a certain temperature to form glass. The formed glass is then cut, ground, and polished to form a thin sheet with a thickness of 1.1 mm. The transmission spectrum of the thin sheet is measured by an ultraviolet spectrophotometer, and the measured transmittance is converted to a thickness of 1.1 mm. The four corners and the center are within the error range of ±0.05 mm.
[0016] Preferably, in step 2), the mixing time of the glass mixture and the raw materials of the composite decolorizing agent is 30-40 minutes. The mixing device is a laboratory stirrer or disperser, which is a common laboratory equipment and is not limited here.
[0017] Preferably, in the step 3), the melting temperature of the glass and decolorizing agent mixture in the crucible is 1550°C-1630°C, the melting holding time is 6h-8h, the clarification and homogenization temperature of the glass and decolorizing agent mixture in the crucible is 1530°C-1620°C, and the clarification and homogenization time is 4h-8h. The crucible can be a platinum crucible, etc., which is not limited here.
[0018] Preferably, in the step 4), the annealing temperature of the glass liquid is 630° C.-700° C., and the annealing time is 12 h-24 h.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The SiO2 of the present invention is introduced by ordinary white sand with a low cost and an iron content of 800ppm. The SiO2 is cheap and is not easy to cause corrosion damage to the kiln during melting. The oxidizability of the glass is increased by adding CeO2, so that the Fe in the glass is 2+ Fe 3+ The glass becomes lighter in color, and then the glass is dyed blue by Co2O3, which neutralizes the light yellow color of the glass, and Nd2O3 appears blue-purple in the glass to eliminate Fe 3+ The composite decolorizing agent combination has both clarifying and stable decolorizing effects, and can effectively improve the whiteness, transparency and uniformity of the glass. The prepared aluminosilicate glass has a transmittance T≥91% at a thickness of 1.1 mm, and the color of the aluminosilicate glass can be controlled at a high iron content, and has a stable decolorizing effect, thereby reducing production costs;
[0021] The application method of the composite decolorizing agent of the present invention is easy to operate, and only the ratio of the composite decolorizing agent to the glass mixed liquid needs to be adjusted to uniformly carry out stirring and heating processing, which is convenient for mass production. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] A composite decolorizer for high-iron aluminosilicate glass comprises a glass mixture of high-iron aluminosilicate glass and a composite decolorizer added to the glass mixture, wherein the composite decolorizer consists of CeO2, Co2O3 and Nd2O3, wherein the content of CeO2 is 0.05%-0.15% of the glass mixture, the content of Co2O3 is 1.5ppm-2.5ppm of the glass mixture, and the content of Nd2O3 is 0.01%-0.02% of the glass mixture.
[0024] SiO2 is the main component of the glass skeleton. As the largest component of glass, it helps to reduce the thermal expansion coefficient of glass and improve the strength and chemical stability of glass. When the SiO2 content is too low, the mechanical strength and weather resistance of the glass deteriorate and the thermal expansion coefficient increases. When the SiO2 content is too high, the melting temperature is high, and defects such as bubbles and stones are easily generated, which is not conducive to industrial production. Therefore, the SiO2 content of the present invention is in the range of 57%-64%.
[0025] Al2O3 is beneficial to improve the structural strength of glass, promote the integrity of glass network, enhance the chemical stability, elastic modulus and hardness of glass, and free oxygen and Al 3+ The formation of glass former AlO4 forms larger void channels in the network structure of the glass, which is beneficial to the exchange of alkali metal ions to obtain the maximum CS and DOL. In aluminosilicate glass, if the Al content is too high, the glass viscosity will increase, the melting temperature will increase, and the industrial production will be more difficult; if the Al content is too low, the ion exchange depth in chemical strengthening will be greatly reduced. Therefore, the Al2O3 contained in the present invention is in the range of 13%-15%.
[0026] Na2O is a network exosome that promotes the melting of glass raw materials and has a great effect on chemical strengthening. If the content of Na2O exceeds 17%, the weather resistance and stability of the glass will deteriorate. If it is less than 13%, it is not conducive to glass melting, and the strength of chemical strengthening is also reduced. Therefore, the optimal range of the Na2O content of the present invention is 12-14%
[0027] K2O and Na2O are components of the same nature. When K2O and Na2O are added together, the high-temperature melting and clarification of the glass are improved through the mixed alkali effect, and the chemical strengthening effect is promoted. If the content of K2O is too high, the ion exchange capacity of the glass will decrease, and the linear expansion coefficient will increase. Therefore, the preferred range of K2O contained in the present invention is 4%-6%.
[0028] MgO, as an alkaline earth metal oxide, helps to lower the melting temperature of glass, reduce the tendency of glass crystallization, and at the same time can increase the elastic modulus of glass and inhibit the generation of cracks. However, if the content is too high, the linear expansion coefficient of the glass will be too high, and if it is too low, the viscosity of the glass melt will increase. Therefore, the content of MgO in the present invention is 4%-7%;
[0029] ZrO2 can improve the chemical stability of glass, increase the surface hardness of glass, and resist the formation and expansion of cracks in glass, thus making glass more scratch-resistant. It is a necessary component, and ZrO2 can increase the ion exchange rate of glass. However, too high a content of ZrO2 will significantly increase the melting temperature of glass. Therefore, the ZrO2 contained in the present invention is in the range of 0%-1.5%.
[0030] CeO2 has a good decolorization effect. It releases oxygen as the melting temperature of the glass, and makes Fe 2+ Iron oxides are converted into Fe 3+ , usually used together with nitrates, the amount of introduction is 0.05%-0.15% of the total weight of the mixture,
[0031] Co2O3 introduces Co2 + , make the glass blue, neutralize the light yellow color of the glass, the decolorization is stable, adding too much glass transmittance T% decreases, the amount of Co2O3 added is 1.5-2.5ppm of the total weight of the mixture;
[0032] Nd2O3 introduces Nd 3+ It is also a good decolorizing agent. Its absorption spectrum is very narrow and can accurately compensate for Fe 3+ The coloring of the glass is blue-purple to eliminate Fe 3+ Its yellow-green color, in addition, its discoloration does not change with the melting conditions, nor with the composition of the glass. If too much Nd2O3 is added, the glass transmittance T% will decrease, affecting the quality of the glass. The amount of Nd2O3 added to the mixture is 0.01%-0.02%.
[0033] The glass mixture is composed of SiO2, Al2O3, Na2O, K2O, MgO and ZrO2, wherein the content of SiO2 is 57%-64%, the content of Al2O3 is 13%-15%, the content of Na2O is 12%-14%, the content of K2O is 4%-6%, the content of MgO is 4%-7% and the content of ZrO2 is 0%-1.5%. SiO2 is introduced from a high-iron raw material with low cost and high iron content, which is not limited here. According to the high-iron raw material with different iron content, the bad color in the produced glass can be neutralized by adjusting the proportion of each raw material of the composite decolorizer.
[0034] The SiO2 in the present invention is introduced by 800ppm of ordinary white sand, and the iron content of the prepared aluminosilicate glass is 590-660ppmm, showing a poor green color. By adding CeO2, Fe 2+ Fe 3+ The glass becomes lighter in color, and the blue-purple color produced by Co2O3 and Nd2O3 eliminates Fe 3+ The yellow-green color of the glass is improved, thereby improving the whiteness of the glass.
[0035] A method for applying the composite decolorizing agent based on the high-iron aluminosilicate glass as described above comprises the following steps:
[0036] 1) Weigh 1000g of glass mixture, and weigh the raw materials in the composite decolorizer in proportion to the weight of the glass mixture;
[0037] 2) placing the glass mixture and the raw materials of the composite decolorizing agent in a mixing device and mixing them for a certain period of time to form a glass and decolorizing agent mixture;
[0038] 3) placing the glass and decolorizing agent mixture into a crucible and heating it to a certain temperature for melting and processing, and after melting, lowering the temperature to a certain level for clarification and homogenization to form glass liquid;
[0039] 4) The clarified and homogenized glass liquid is poured into a mold to form a preliminarily formed glass, and the preliminarily formed glass is placed in a heating device to gradually anneal and cool to room temperature at a certain temperature to form glass. The formed glass is then cut, ground, and polished to form a thin sheet with a thickness of 1.1 mm. The transmission spectrum of the thin sheet is measured by an ultraviolet spectrophotometer, and the measured transmittance is converted to a thickness of 1.1 mm. The four corners and the center are within the error range of ±0.05 mm.
[0040] In the step 2), the mixing time of the glass mixture and the raw materials of the composite decolorizing agent is 30-40 minutes. The mixing device is a laboratory mixer or disperser, which is a common laboratory equipment and is not limited here.
[0041] In the step 3), the melting temperature of the glass and decolorizing agent mixture in the crucible is 1550°C-1630°C, the melting holding time is 6h-8h, the clarification and homogenization temperature of the glass and decolorizing agent mixture in the crucible is 1530°C-1620°C, and the clarification and homogenization time is 4h-8h. The crucible can be a platinum crucible, etc., and is not limited here.
[0042] In the step 4), the annealing temperature of the glass liquid is 630° C.-700° C., and the annealing time is 12 h-24 h.
[0043]
[0044]
[0045]
[0046] The above table shows the chromaticity coordinates and transmittance results of the 14-component glass prepared by different ratios of glass mixtures and composite decolorizers in the present invention, which were sliced into 1.1 mm slices and tested on the slices.
[0047] As shown in the table above, the glass prepared by the glass mixture and the composite decolorizing agent of the present invention has a transmittance T ≥ 91% at a thickness of 1.1 mm, has good transmittance, controls the absolute value of a within 0.07, and the value of b is close to 0.1. It is visually white, realizes color control of aluminosilicate glass at a high iron content, and has a stable decolorization effect.
[0048] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0049] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A composite decolorizing agent for high-iron aluminosilicate glass, comprising a glass mixture of high-iron aluminosilicate glass and a composite decolorizing agent added to the glass mixture, characterized in that: The composite decolorizing agent consists of CeO2, Co2O3 and Nd2O3, wherein the content of CeO2 is 0.05%-0.15% of the glass mixture, the content of Co2O3 is 1.5ppm-2.5ppm of the glass mixture, and the content of Nd2O3 is 0.01%-0.02% of the glass mixture.
2. The composite decolorizing agent for high-iron aluminosilicate glass according to claim 1, characterized in that: The glass mixture consists of SiO2, Al2O3, Na2O, K2O, MgO and ZrO2, wherein the content of SiO2 is 57%-64%, the content of Al2O3 is 13%-15%, the content of Na2O is 12%-14%, the content of K2O is 4%-6%, the content of MgO is 4%-7% and the content of ZrO2 is 0%-1.5%.
3. An application method of the composite decolorizing agent for high-iron aluminosilicate glass according to any one of claims 1 to 2, characterized in that: The steps include: 1) Weigh a certain weight of glass mixture, and weigh each raw material in the composite decolorizer in proportion to the weight of the glass mixture; 2) placing the glass mixture and the raw materials of the composite decolorizing agent in a mixing device and mixing them for a certain period of time to form a glass and decolorizing agent mixture; 3) Putting the glass and decolorizing agent mixture into a container and heating it to a certain temperature for melting and processing, and lowering the temperature to a certain level after melting to clarify and homogenize, thereby forming glass liquid; 4) The clarified and homogenized glass liquid is poured into a mold to form a preliminarily formed glass, and the preliminarily formed glass is placed in a heating device to gradually anneal and cool to room temperature at a certain temperature to form glass.
4. The application method according to claim 3, characterized in that: In the step 2), the mixing time of the glass mixture and the raw materials of the composite decolorizing agent is 30 minutes to 40 minutes.
5. The application method according to claim 3, characterized in that: In the step 3), the melting temperature of the glass and decolorizing agent mixture in the container is 1550℃-1630℃, the melting holding time is 6h-8h, the clarification and homogenization temperature of the glass and decolorizing agent mixture in the crucible is 1530℃-1620℃, and the clarification and homogenization time is 4h-8h.
6. The application method according to claim 3, characterized in that: In the step 4), the annealing temperature of the glass liquid is 630° C.-700° C., and the annealing time is 12 h-24 h.
Citation Information
Patent Citations
Ultra-white glass
CN102092941A
Glass for chemical strengthening, chemically strengthened glass, production method of glass for chemical strengthening, production method of chemically strengthened glass, production lass for display devices, and display device
CN105948488A
Glass composition and preparation method thereof
CN106587612A
Low-iron, ultrawhite and superhigh aluminum glass and preparation method and application thereof
CN106904830A
Low-viscosity and high-aluminum glass, preparation method and applications thereof
CN111018346A
Cited By
Method for improving whiteness of aluminosilicate glass with iron content of 150-300ppm
CN122277098A